2016
DOI: 10.1515/bnm-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel-based microfluidics for vascular tissue engineering

Abstract: Abstract:In this work, we have explored 3-D co-culture of vasculogenic cells within a synthetically modified fibrin hydrogel. Fibrinogen was covalently linked with PEG-NHS in order to improve its degradability resistance and physico-optical properties. We have studied influences of the degree of protein PEGylation and the concentration of enzyme thrombin used for the gel preparation on cellular responses. Scanning electron microscopy analysis of prepared gels revealed that the degree of PEGylation and the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
1
27
0
Order By: Relevance
“…Previously, we have shown that the 5 : 1 PEGylated brin gel possesses a high angiogenic potential compared to the native brin gel. 11,14,15 However, the structural rearrangement caused by brin modication remained unclear. The results presented in this study allowed us to suggest that the inner structure of the PEGylated 5 : 1 brin gel can be presented by exible macroparticles with a smaller space between them.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have shown that the 5 : 1 PEGylated brin gel possesses a high angiogenic potential compared to the native brin gel. 11,14,15 However, the structural rearrangement caused by brin modication remained unclear. The results presented in this study allowed us to suggest that the inner structure of the PEGylated 5 : 1 brin gel can be presented by exible macroparticles with a smaller space between them.…”
Section: Resultsmentioning
confidence: 99%
“…10 Natural brin rapidly degrades and is not transparent, so several modications have been suggested to overcome these limitations and, moreover, those have been shown to increase its angiogenic potential. [11][12][13] Among them, PEGylation (modication with functionalized polyethylene glycol (PEG)) is of particular interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fibrin gels undergo degradation and strong matrix remodeling in vitro , which results in construct shrinkage and weight loss. PEGylation of fibrinogen is one possible method to control the gel stability without impairment of its excellent cytocompatible properties [ 28 ]. In this study PEGylated fibrin was evaluated highly cytocompatible with gingival fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The PureCol—Matrigel mixture was prepared by mixing the bovine collagen type I solution (PureCol, 5005-100ML, Advanced BioMatrix Inc, USA), Matrigel, and cell culture medium on ice to final concentrations of 0.67 mg/mL and 4.7 mg/mL, respectively. The PEGylated fibrin hydrogel was prepared as previously described [ 28 ]. The human gingival fibroblasts (5000 cells in 150 μL culture medium) were seeded on 50 μL of PEGylated fibrin hydrogels after gelation in 96-well plates and cultured for 24 or 72 hours at 37 °C in a humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%